Silver(i)–N-heterocyclic carbene catalyzed multicomponent reactions: a facile synthesis of multisubstituted pyridines. Issue 127 (14th December 2015) - Kankala, Shravankumar; Pagadala, Ramakanth; Maddila, Suresh; Vasam, Chandra Sekhar; Jonnalagadda, Sreekantha B.
Abstract : A room temperature four component reaction between aromatic aldehydes, CH2 (CN)2 and NH4 OAc with ketones mediated by Ag(i )–NHC pre-catalysts to produce multisubstituted pyridines in a short reaction time in eco-friendly ethanol was described. Abstract : A four component one-pot reaction between aromatic aldehyde, malononitrile, ammonium acetate and ketone mediated by Ag(i ) N-heterocyclic carbene to produce multisubstituted and fused pyridines in a short reaction time (∼10 min) in ethanol at room temperature is described.